2020
DOI: 10.18433/jpps30965
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Ionic Liquids in Pharmaceutical Dosage Forms for Small Molecule Drug and Vaccine Delivery System

Abstract: Ionic liquids are salts in which the ions are poorly coordinated, which causes them to exist in liquid form below 100°C, or at room temperature. Therefore, these are also defined as room temperature ionic liquids (RTILs). In ionic liquids, at least one ion has a delocalized charge and one component is organic, which prevents the formation of a stable solid form of crystal lattice. Physical properties of ionic liquids, such as melting point, viscosity, and solubility of starting materials and other solvents, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 120 publications
0
13
0
Order By: Relevance
“…Ionic liquids (ILs) have gained significant attention for topical and transdermal delivery due to their potential benefits, including a broad safety profile and their ability to tune the physiological properties of active pharmaceutical ingredients 12,103,104 . Moreover, ILs in vaccine dosage forms can act as stabilizer, solubilizer, targeted delivery inducer and permeation enhancer 105 . Tahar et al 106 used choline-fatty acids ( [Cho][FA]) as a biocompatible IL to mediate the dissolution of a water-soluble antigen peptide in an oil-based skin penetration enhancer.…”
Section: Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids (ILs) have gained significant attention for topical and transdermal delivery due to their potential benefits, including a broad safety profile and their ability to tune the physiological properties of active pharmaceutical ingredients 12,103,104 . Moreover, ILs in vaccine dosage forms can act as stabilizer, solubilizer, targeted delivery inducer and permeation enhancer 105 . Tahar et al 106 used choline-fatty acids ( [Cho][FA]) as a biocompatible IL to mediate the dissolution of a water-soluble antigen peptide in an oil-based skin penetration enhancer.…”
Section: Ionic Liquidsmentioning
confidence: 99%
“… 12 , 103 , 104 Moreover, ILs in vaccine dosage forms can act as stabilizer, solubilizer, targeted delivery inducer, and permeation enhancer. 105 Tahar et al 106 used choline‐fatty acids ([Cho][FA]) as a biocompatible IL to mediate the dissolution of a water‐soluble antigen peptide in an oil‐based skin penetration enhancer. The authors screened a range of fatty acids, among which, oleic acid (C18:1) was found to be the most suitable anion due to its low cytotoxicity, affinity to the oil‐based skin permeation enhancer (isopropyl myristate) and ability to promote the permeation of antigens through skin without irritation in vivo.…”
Section: Noninvasive Transcutaneous Immunizationmentioning
confidence: 99%
“…Several experimental studies explored the thermal stability of phosphonium-based ILs with different anion structures. 42,45,46 Such studies employed various experimental methods including thermogravimetric analysis (TGA), 46 gas chromatography-mass spectroscopy (GC-MS), 47 thermogravimetric-mass spectrometry (TG-MS), 48 pyrolysis gas chromatography (PyGC), 49 thermal desorption-mass spectroscopy (TD-MS), 50 Fourier transform infrared spectroscopy (FTIR), 51,52 and time-of-flight mass spectrometry (TOF-MS). 53 These techniques were used to explore parameters such as decomposition temperature, 46 decomposition products, 47,50 and evolution of chemical structure during the heating.…”
Section: Introductionmentioning
confidence: 99%
“…42,45,46 Such studies employed various experimental methods including thermogravimetric analysis (TGA), 46 gas chromatography-mass spectroscopy (GC-MS), 47 thermogravimetric-mass spectrometry (TG-MS), 48 pyrolysis gas chromatography (PyGC), 49 thermal desorption-mass spectroscopy (TD-MS), 50 Fourier transform infrared spectroscopy (FTIR), 51,52 and time-of-flight mass spectrometry (TOF-MS). 53 These techniques were used to explore parameters such as decomposition temperature, 46 decomposition products, 47,50 and evolution of chemical structure during the heating. [51][52][53] Atomistic simulations, both ab initio and classical molecular dynamics (MD), have been employed to study the thermal decomposition of phosphonium-based ILs.…”
Section: Introductionmentioning
confidence: 99%
“…As such, ILs have become viable alternative solvents or co-solvent to conventional organic solvents in different fields of life sciences. In addition, it is interesting to note that a wide variety of cations and anions can be used to form ILs and that each one has unique properties that can meet specific requirements for use in biochemistry, biotechnology, medicine, pharmacology, and bio-nanotechnology, etc., applications [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The applications and relevant functions of ILs in biomolecular systems are based on the nature of the specific interaction that occur between ILs and biomacromolecules.…”
Section: Introductionmentioning
confidence: 99%